NON-DRUG HABILITATION OF CHILDREN WITH PERINATAL AFFECTIONS OF THE NERVOUS SYSTEM - Irina A. Belyaeva; Elena P. Bombardirova; Elena I. Tokovaya; Natalia A. Kharitonova; Svetlana B. Lazurenko; Tatiana V. Turti; Maria S. Illarionova (Вопросы современной педиатрии, 2017)
Drug-free rehabilitation treatment modalities of children with perinatal pathology of the nervous system are considered as an important component of the habilitation process and creation of a developing environment for infants with a high risk of disabling conditions. Corrective actions depend not only on the severity of perinatal pathology but also on the maturity of a child and individual characteristics of neuroonthogenesis. The article considers the main drug-free technologies of rehabilitation treatment — both already known and recently developed including methods of kinesi-, aqua-, music therapy, and correctional pedagogy. A separate section is devoted to breastfeeding as an important component of the adequate development of a child. A necessary condition for effective habilitation is a family-oriented approach, which implies active participation of parents in the implementation of rehabilitation programs for children.